Bank risk taking and deposit insurance premium: Comparison between Islamic and conventional bank / Sharifah Adlina binti Syed Abdullah - Syed Abdullah, Sharifah Adlina (2014)
Liquidity assistance is provided for under the lender of last resort facility for solvent banks. Nevertheless, deposit insurance is a depositors’ protection tool to sustain depositors’ confidence in the banking system and to ensure there is financial stability in the market. Similar to other types of insurance, deposit insurance suffers from the moral hazard problem. Aptly, a credible design feature of deposit insurance coupled with prudential regulation and supervision would limit this problem. For this reason, this thesis aims to investigate three objectives related to the moral hazard problem associated with deposit insurance. The first objective is, to investigate the presence of moral hazard by way of increase in bank risks through credit risk, insolvency risk and operational risk. Secondly, is to compare the changes in bank risk, both in the conventional and Islamic banks post deposit insurance. The last objective is to examine the credibility of the risk based deposit insurance premium in mitigating the moral hazard problem. To overcome the endogeneity problem in panel data, instrumental variables that are the lagged explanatory variable in a dynamic panel data methodology are used. Specifically, this thesis employs the System Generalized Method of Moment (GMM) estimator. Based on literature, System GMM has the least biased estimator among other alternatives. The sample includes all the mandatory members (conventional and Islamic banks in Malaysia) of deposit insurance protection over the period 2002-2010. To achieve the first and second objectives, this thesis used unbalanced panel data for the all banks sample and Islamic banks sample while the panel data is balanced for conventional banks. During the financial crisis 2007/2008, Islamic banking grew in importance as an alternative to conventional banking that appeared riskier than the Islamic banks. However, the impact of deposit insurance system on Islamic banks has not been analyzed as rigorously as that on conventional banks. For the all banks sample, the main findings are that the bank risk through insolvency risk and operational risk is significant and positively associated with the introduction of a deposit insurance system. Specifically, it provides new insights into various implications of deposit insurance on Islamic banks risk taking. This study includes new empirical evidence on operational risk taking by conventional banks post deposit insurance system. An important aspect of the new financial landscape is the increased focus on financial stability. A deposit insurance system accomplishes this purpose with the deposit insurance premium exerting as an important tool in mitigating the moral hazard problem. This leads to the final objective of this study. The banks’ annual premium amounts are estimated to determine whether the premium is sensitive towards bank risk in the risk-based premium. This thesis provides very strong evidence that risk-based deposit insurance does not necessarily mitigate the moral hazard problem unless the quantum of risk-premium is adequate to cover the increased risk. Therefore, this thesis offers not only the understanding of the deposit insurance concept and theory but also provides new insights based on original empirical evidence. The results have several important policy implications.